Everyday routines and material practices in the design studio: Why informal pedagogy matters - Corazzo, James; Gharib, Layla (Design and Technology Education: An International Journal, 2021)
This study aims to improve understanding of the design studio as a setting where formal and informal pedagogies intersect. We argue that the informal dimension of learning has an essential but under-acknowledged role in contributing to the development of design students. Our research focuses on students' everyday routines and their associated material practices in both a proximate studio setting (physical), – such as making tea, speaking to peers, doing work – and in a distance (online) setting. We frame these activities as informal pedagogy that supports design learning and the development of designerly identities. While this study focuses on students' accounts of their everyday use of the physical studio (pre-pandemic), it is augmented with students' accounts of distance design education (during the pandemic). The disruption to studio practices, and the subsequent use of alternative environments to learn design, provided an opportunity to reconsider everyday routines and material practices at both proximate and distance settings. Supported by the infrastructure of the physical studio, we identify five 'functions' of informal pedagogy and use this to observe how these functions operated in distance settings. To understand the intersection between formal and informal pedagogy, we argue that binary terms are unhelpful and instead argue for an axis that runs from formal to structured informal to unstructured informal to social.